Changes in Oral Anticoagulant Prescribing for Stroke Prevention in Patients With Atrial Fibrillation - Admassie, E.; Stafford, Leanne; Bereznicki, L. (Excerpta Medica, Inc, 2017)
© 2017 Elsevier Inc. Suboptimal guideline adherence and underuse of anticoagulants in patients with atrial fibrillation (AF) have been reported worldwide. This study aimed to compare anticoagulation practice in Australia during the pre- and postdirect oral anticoagulant (DOAC) eras. Between January 2011 and July 2015, patients with nonvalvular AF (NVAF) admitted to the Royal Hobart Hospital, Tasmania, Australia, were retrospectively reviewed. The pre- and post-DOAC era cohorts included admissions from January 2011 to July 2013 and August 2013 to July 2015, respectively. Overall, 2,118 patients met our inclusion criteria. The overall rate of anticoagulation increased from 52.5% in the pre-DOAC era to 60.7% in the post-DOAC era (p < 0.001). Moreover, prescribing of OACs among high-risk patients improved significantly (63.1% vs 55.2%, p = 0.001). OAC overprescribing in low-risk patients did not change significantly between the 2 cohorts (35.0% vs 42.9% in the pre- and post-DOAC eras, respectively, p = 0.59). In multivariate analysis, DOAC era (odds ratio [OR] 1.40, 95% confidence interval [CI] 1.17 to 1.68 and CHA 2 DS 2 -VASc =2 (OR 1.95, 95% CI 1.36 to 2.80) were independent predictors of OAC prescribing in both eras and the whole study period. Conversely, aging and previous bleeding were inversely associated with OAC prescribing. In conclusion, there has been a significant increase in OAC prescribing in the post-DOAC era, potentially driven by the widespread availability of DOACs. However, OAC underuse in high-risk patients and overuse in low-risk patients was apparent throughout our study. These findings highlight the need to identify the drivers of anticoagulant underuse and overuse and address them accordingly.